SINERGI GURU BK DAN GURU PAI DALAM MEMBANGUN KESADARAN TERHADAP LAYANAN BIMBINGAN DAN KONSELING UNTUK MENANGANI PERILAKU BULLYING DI SEKOLAH - rosa lina; Dyah Kusumaningtyas; Rahmi Anekasari (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
This research is motivated by students' low awareness of the function of Guidance and Counseling (BK) services as a means of support and problem-solving, particularly in addressing bullying behavior in schools. This situation results in students underutilizing BK services when facing social and psychological problems. This study aims to analyze the synergy between Guidance and Counseling (BK) teachers and Islamic Education (PAI) teachers in building student awareness of BK services to address bullying behavior in schools. This study used a qualitative approach with a library research approach. The research object was the synergy between BK and PAI teachers in addressing bullying, while the study subjects were various relevant scientific sources. Data were collected through documentation techniques from journals, books, scientific articles, and previous research findings. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that students' awareness of BK services is influenced by their understanding of the function of BK, the support of the school environment, and the teacher's approach. Synergy between guidance counselors and Islamic Religious Education (PAI) teachers can increase student awareness through character development, instilling the values ​​of empathy, tolerance, and compassion, and educating students about the importance of seeking help when facing bullying. This collaboration contributes to creating a safe, comfortable, and supportive school environment for student development. Therefore, synergy between guidance counselors and Islamic Religious Education (PAI) teachers is a crucial strategy for increasing the effectiveness of guidance and counseling services in addressing bullying behavior in schools. Keywords: synergy between guidance counselors, Islamic Religious Education (PAI) teachers, guidance and counseling services, student awareness, bullying.